Meniscus cell regional phenotypes: Dedifferentiation and reversal by biomaterial embedding. Issue 10 (25th December 2020) - Andress, Benjamin; Kim, Jason H.; Cutcliffe, Hattie C.; Amendola, Annunziato; Goode, Adam P.; Varghese, Shyni; DeFrate, Louis E.; McNulty, Amy L.
Abstract: Meniscus injuries are common and a major cause of long‐term joint degeneration and disability. Current treatment options are limited, so novel regenerative therapies or tissue engineering strategies are urgently needed. The development of new therapies is hindered by a lack of knowledge regarding the cellular biology of the meniscus and a lack of well‐established methods for studying meniscus cells in vitro. The goals of this study were to (1) establish baseline expression profiles and dedifferentiation patterns of inner and outer zone primary meniscus cells, and (2) evaluate the utility of poly(ethylene glycol) diacrylate (PEGDA) and gelatin methacrylate (GelMA) polymer hydrogels to reverse dedifferentiation trends for long‐term meniscus cell culture. Using reverse transcription‐quantitative polymerase chain reaction, we measured expression levels of putative meniscus phenotype marker genes in freshly isolated meniscus tissue, tissue explant culture, and monolayer culture of inner and outer zone meniscus cells from porcine knees to establish baseline dedifferentiation characteristics, and then compared these expression levels to PEGDA/GelMA embedded passaged meniscus cells. COL1A1 showed robust upregulation, while CHAD, CILP, and COMP showed downregulation with monolayer culture. Expression levels of COL2A1, ACAN, and SOX9 were surprisingly similar between inner and outer zone tissue and were found to be less sensitive as markers of dedifferentiation. When embedded in PEGDA/GelMA hydrogels, expression levels of meniscus cell phenotype genes were significantly modulated by varying the ratio of polymer components, allowing these materials to be tuned for phenotype restoration, meniscus cell culture, and tissue engineering applications.